Enhancing start performance in the sport of skeleton - Colyer, S. L. (2015)
A fast start is considered to be crucial in skeleton with marginal gains in start performance perceived to make meaningful improvements to overall chances of success. Currently, knowledge surrounding the underlying determinants of start performance is sparse and training practices are based on limited scientific evidence. A series of investigations were conducted to advance this understanding. Initial observations revealed similarities between dry-land push-starts and those on ice tracks. However, the number of steps taken before loading was adjusted to seemingly accommodate unique track profiles and appeared to be influenced by physical capacity. Consequently, skeleton athletes completed multiple two day testing sessions (four physical tests and biochemical analyses) across two seasons, alongside dry land push track tests. Additionally, body composition was assessed either side of selected training and competition blocks. Three independent physical factors (countermovement jump, sprint and force-power characteristics) were identified as fundamental to a fast push start and a regression equation comprising these variables provided an accurate prediction of start ability (R^2 = 0.86). Testosterone appeared to influence push track performance and lean mass accrual, however, retrospective biochemical analyses were deemed to have limited utility in applied practice. Conversely, the importance of monitoring body composition, particularly across competition seasons, was apparent and dual energy X ray absorptiometry is an appropriate tool to detect meaningful changes. A continuous sled velocity measure confirmed the contribution of physical capabilities to both the distance and velocity attained before loading. Importantly, loading phase success appeared independent of physical ability, perhaps warranting specific loading technique training. Finally, a trade off between pre load velocity and load effectiveness was evident, and experimentally modifying loading distance provided a promising approach to improve performance in developing athletes. This thesis has informed skeleton training by identifying factors which contribute to performance, alongside approaches to thoroughly evaluate athlete progression and has introduced processes through which start performance can be enhanced.